2010
DOI: 10.1002/jca.20238
|View full text |Cite
|
Sign up to set email alerts
|

The treatment of acute liver failure with fractionated plasma separation and adsorption system: Experience in 85 applications

Abstract: FPSA system is a safe and effective detoxification method for patients with liver dysfunction, including ALF. The system is useful as a symptomatic treatment before liver transplantation; in up to 1/3 of the cases, it can even be used as a sole method of treatment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0
2

Year Published

2011
2011
2024
2024

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 39 publications
(15 citation statements)
references
References 31 publications
0
13
0
2
Order By: Relevance
“…It is indeed possible that longer and repeated FPSA sessions might have had a larger impact, but it is most often not straightforward to include a 5-h extra-corporeal blood purification session in the often highly complicated intensive care of ALF patients. However, other centres have been able to treat patients with FPSA repetitively for several days and actually achieved a significant improvement of parameters known to influence the prognosis [25,26]. In a wider perspective, the current trend in the advances in the handling of ALF patients might, eventually, lead to a therapeutic timeframe large enough for a sufficient number of liver assist sessions to achieve clinically relevant effects.…”
Section: Discussionmentioning
confidence: 99%
“…It is indeed possible that longer and repeated FPSA sessions might have had a larger impact, but it is most often not straightforward to include a 5-h extra-corporeal blood purification session in the often highly complicated intensive care of ALF patients. However, other centres have been able to treat patients with FPSA repetitively for several days and actually achieved a significant improvement of parameters known to influence the prognosis [25,26]. In a wider perspective, the current trend in the advances in the handling of ALF patients might, eventually, lead to a therapeutic timeframe large enough for a sufficient number of liver assist sessions to achieve clinically relevant effects.…”
Section: Discussionmentioning
confidence: 99%
“…Sentürk el al. compared the biochemical and clinical parameters for FPSA in patients with ALF and acute-on-chronic liver failure, and showed a significant improvement in the biochemical parameters in HE, although survival rates were not addressed in this study [40]. Similarly, Komardina et al also showed hemodynamic and biochemical improvements with Prometheus in patients with ALF, but without any difference in survival outcomes [41].…”
Section: Fractionated Plasma Separation and Adsorption-fpsa (Prometheus)mentioning
confidence: 70%
“…One series described FPSA treatment in 18 patients, eight of them presenting with fulminant hepatitis B. Even though only one liver transplantation was performed, 50% 1-month survival after a mean of three FPSA sessions was observed (15).…”
Section: Clinical Resultsmentioning
confidence: 99%